PERAN PERBANKAN DALAM MENGEMBANGKAN SEKTOR USAHA KECIL-MIKRO YANG BERWAWASAN LINGKUNGAN - Sarwono, Aris Eddy (Universitas Slamet Riyadi, 2010)
ABSTRACT The Bank has a role as intermediary in connection with the debtor. Businesses that have a negative impact on the environment will cause un consistence business, which in turn will affect the banks as creditors. Liabilities for environmental management by industry-large and medium scale industries have been regulated in legislation. For banking policy that requires little effort to preserve the micro-environment is also not yet accommodated. Banking policies in order to encourage the debtor to carry out environmental management is also inadequate. Keywords: Bank, industry large and medium scale, environmental.